Steinbeck cottage, Pacific Grove, Ca. - Richard L. Allman:::Creator::::::::::::
Interior living room and entry way of the Steinbeck Family cottage on 11th St. in Pacific Grove, Ca. Steinbeck and his father built the fireplace and John designed the copper hood of the fireplace. Steinbeck's favorite chair to the right. RESTRICTED USE